Advancing Accessibility: A Systematic Review of Healthcare Accessibility for Individuals with Disabilities and a Proposed Collaborative Partnership Model (Journal of Advanced Research in Social Sciences, 2025)
Despite the Americans with Disabilities Act (ADA) and other policy efforts, healthcare facilities in the U.S. often fail to provide adequate accommodations for individuals with disabilities, resulting in preventable health issues and diminished quality of life. This study aims to synthesize existing literature on healthcare disparities faced by disabled individuals, focusing on barriers such as insufficient physical accommodations, communication challenges, and a lack of disability awareness among healthcare providers. A systematic review was conducted using PRISMA guidelines, with 23 research papers selected from 2006 to 2022. The analysis identified recurring themes of inadequate accessibility, with legal frameworks like the ADA being insufficient in addressing the complexity of these challenges. Key gaps include a lack of scalable, collaborative interventions and insufficient research on disability populations. To address these limitations, this study proposes a novel partnership model that integrates academic institutions, advocacy groups, and healthcare education providers to promote inclusive healthcare environments. The findings highlight the critical need for collaboration across sectors to improve healthcare accessibility for all individuals with disabilities.